Intensification of Evaporation and Condensation Processes in Heat Exchange Apparatus - L. L. Vasiliev; A. G. Kulakov (Наука и техника)
The paper describes proposed design solutions for an intensification of heat transfer in evaporation and condensation heat exchangers. Complex experimental research of heat and mass transfer processes in flat and round cross-section miniature heat pipes is carried out. Optimization, development, manufacturing and an experimental investigation of copper miniature heat pipes with sintered powder are executed. Investigation results of capillary-porous structure properties that are used in evaporation and condensation heat-exchange apparatus are presented.